Evolving Neologisms and Ephemeral Discourse: WeChat Index Analysis of 2021’s Chinese Internet Buzzwords - Yuniarto, Hendy (Universitas Sebelas Maret, 2025)
This study aims to investigate the evolving neologism, ephemeral discourse, and socio-cultural significance of 10 Chinese internet buzzwords in 2021, which are 双减 (shuāng jiǎn), 躺平 (tǎng píng), 元宇宙 (yuán yǔ zhòu), YYDS (yǒng yuǎn de shén), 社交牛逼症 (shè jiāo niú bī zhèng), 绝绝子 (jué jué zǐ), 跌妈不认 (diē mā bù rèn), 破防 (pò fang), 鸡娃 (jī wá), and Emo (yī mó). Employing a quantitative and qualitative approach, we collected those buzzwords from news articles and analyzed their usage trends using the WeChat Index from 2021 to 2024. This study revealed the creative word formation processes and semantic properties of these neologisms among the netspeak. The WeChat Index data showed that seven out of the ten buzzwords experienced a decline in popularity after two years, while three buzzwords maintained an upward trend. Using the concept of ephemeral discourse and critical discourse analysis, we explored how these buzzwords addressed key social, cultural, and political issues, such as education reform, social pressures faced by youth, and the impact of technology on society. The buzzwords' popularity trends were influenced by factors such as the natural lifecycle of neologisms, shifting public priorities, and societal attitudes.